Beyond traditional teaching: a systematic review of innovative pedagogical practices in higher education [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Josefina Amanda Suyo-Vega; Monica Elisa Meneses-La-Riva; Víctor Hugo Fernández-Bedoya (F1000Research)
Background Pedagogical best practices play a pivotal role in ensuring the academic success of students within the higher education landscape. This study aims to systematically synthesize innovative pedagogical best practices within the university context. Methods We conducted a thorough systematic review using the rigorous PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology. Our review involved comprehensive searches of scientific databases, including Eric, Scopus, and Proquest, covering both Spanish and English publications. We strategically employed Boolean operators like AND and OR to create a robust search equation. Our primary research question guiding this investigation was: “What innovative pedagogical practices have been developed in university settings to improve teaching and learning effectiveness?” This central question led us to delve deeply into the strategies utilized, pedagogical approaches adopted, and the noticeable impact achieved after their implementation. Additionally, we carefully established stringent inclusion and exclusion criteria in accordance with PRISMA guidelines to ensure methodological rigor. Results A total of 25 scholarly articles that met the pre-established criteria were meticulously identified and included in this systematic review. The results were thoughtfully categorized into three distinct teaching strategies: the first emphasizing student-centered approaches, the second showcasing the integration of educational technology, and the third highlighting evaluation and feedback methodologies. Conclusions This systematic exploration of pedagogical best practices underscores their paramount importance in driving continuous improvement in teacher training and fostering innovation within the educational arena. Such practices not only create an engaging and effective learning environment but also set the stage for ongoing advancements in the teaching and learning processes.